Quantitative insights into televised birth: a content analysis of One born every minute - De Benedictis, Sara; Johnson, Catherine; Roberts, Julie; Spiby, Helen (Routledge, 2018)
This paper explores birth representations through a content analysis of two seasons of the UK program, One Born Every Minute (Channel 4, 2010- ) (OBEM). Reality television (RTV) has been a fertile ground for the mediation of birth but has also stoked controversy among feminist critics and the birth community about how birth is represented and the impacts this might have for women and society. International research has explored problematic overrepresentation of white, heterosexual couples, as well as noting a predominance of medicalized birth experiences. However, this research is formed largely of qualitative studies that are necessarily based on small samples of episodes. To contribute to this literature, we apply a quantitative and interdisciplinary lens through a content analysis of two seasons of the UK version of OBEM. Paying attention to the geographical and temporal context of OBEM, this paper confirms overrepresentation of white, heterosexual couples and medicalized birth on RTV birth shows while also providing novel insights into the ambiguous representation of birthplace and lead caregivers, the medicalization of birth through the routinization of supposedly minor birth interventions, and the absence of the representation of women’s choice over such interventions.